JSE 27:1 Spring 2013 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2013)
Periodicals of various sorts have long recognized the need to address certain topics on a regular basis. That’s why computer magazines routinely offer articles such as “Windows Tips and Tricks,” and “How to Protect Your Data.” Similarly, photography magazines return again and again to articles explaining how to get the most out of wide-angle lenses, how to shoot portraits in natural light, or how to photograph dramatic landscapes. It seems to me that JSE editorials might also need to recycle certain topics from time to time, in part because readership changes, and in part because researchers in areas of frontier science can have conveniently short memories (like everyone else), perhaps especially when it comes to matters that are intellectually or professionally challenging or uncomfortable. The continuing debate over Daryl Bem’s recent precognition experiments (see Bem 2011, and the Editorial in JSE 25:1) and the similar controversy still dogging work on LENR or “cold fusion” suggests that perhaps it’s time to review certain salient facts about the nature of experimental replication in science. What follows is not new. Harry Collins has done outstanding work on this topic (Collins 1992), and I also addressed the issue at length (Braude 2002). For more recent commentary, see also Stefan Schmidt (2009). Apparently, however, what’s both obvious and commonsensical is very easy to overlook.